WORKERS MOTIVATION AND ORGANIZATIONAL PRODUCTIVITY IN CHEMICAL COMPANIES IN RIVERS STATE, NIGERIA. (Journal of the Management Sciences, 2024)
This study examined workers motivation and organizational productivity in chemical companies Rivers State, Nigeria. The researcher selected three measures of workers motivation to determine their relationships on organizational productivity. Three specific objectives, research questions, and three hypotheses were formulated for the study. Notwithstanding the employees committed efforts, most chemical companies are not ready to practice sustainable motivation that may boost productivity. Survey design was exploited and population of the study comprises four hundred and sixty-two (462) selected employees from the designated ten chemical companies in Rivers State. The researcher also applied stratified sampling and the sample size was projected at 214 employeesthrough Taro Yamane’s formula. Instrument for data collection was developed through primary and secondary sources. Statistical tools used to analyze the data include descriptive analysis and spearman rank correlation. The findings unveiled a positive significant relationship between workers motivation and organizational productivity. The researcher concluded that workers motivation predicts organizational productivity and recommend that chemical companies should provide reasonable compensation and conducive work environment that could bring satisfaction and high productivity.
Keywords: Workers, motivation, training, compensation, productivity, Rivers State, Nigeria.